Health workers’ motivation to work in a COVID-19 designated hospital during COVID-19 pandemic - Pokharel, Yagya Raj; Aryal, Prayush; Yadav, Bharat Kumar; Pokharel, Grishma (Nepal Journal of Multidisciplinary Research, 2021)
Introduction: COVID-19 has brought global challenges in the health and safety of people. It has created not only the economic and social disaster in global society but also pose the life of healthcare workers in danger. In such critical situation, health workers were the main fighters who stood against the spread of COVID-19 and were always involved in the care and treatment of COVID patients. The main objective of this study was to explore health workers’ motivational factors to work in COVID designated hospital during COVID-19 pandemic. Method: The study was conducted at Patan Hospital, Lalitpur. The study had collected the qualitative data from in-depth interview of doctors and nurses. Convenience sample method was used to collect the data. Total, 12 health workers (6 Doctors and 6 Nurses) were interviewed till thematic saturation. Collected information was transcribed and thematic analysis was done to analyze factors motivating health workers. Result: The study found three major factors that motivated the health workers: (i) Always remembering oneself as a Health worker (Doctor/Nurse), (ii) Commitment with the hospital and (iii) Own ethics that one has to serve. Conclusion: Despite difficulties and fear, the health workers were internally motivated to serve during the pandemic. However, they think they should be provided with the declared facilities, incentives and motivation plan to further encourage them.